2023
DOI: 10.1186/s12906-023-04143-0
|View full text |Cite
|
Sign up to set email alerts
|

The changes of neuroactivity of Tui Na (Chinese massage) at Hegu acupoint on sensorimotor cortex in stroke patients with upper limb motor dysfunction: a fNIRS study

Yu-Feng Chen,
Meng-Chai Mao,
Guang-Yue Zhu
et al.

Abstract: Background Tui Na (Chinese massage) is a relatively simple, inexpensive, and non-invasive intervention, and has been used to treat stroke patients for many years in China. Tui Na acts on specific parts of the body which are called meridians and acupoints to achieve the role of treating diseases. Yet the underlying neural mechanism associated with Tui Na is not clear due to the lack of detection methods. Objective Functional near-infrared spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Results showed that the hemodynamics of the contralateral M1 were obviously enhanced during massage at the Hegu of the affected arm in stroke patients, but there was no similar pattern in the hemodynamics of the ipsilateral M1. There was a significant difference between the lateralization indices of the affected and healthy sides in stroke patients, indicating that the combination of Tuina and fNIRS could reflect the functional state of the sensory-motor nerve circuit ( Chen Y. F. et al, 2023 ). It should be noted that the team conducted a randomized controlled study.…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that the hemodynamics of the contralateral M1 were obviously enhanced during massage at the Hegu of the affected arm in stroke patients, but there was no similar pattern in the hemodynamics of the ipsilateral M1. There was a significant difference between the lateralization indices of the affected and healthy sides in stroke patients, indicating that the combination of Tuina and fNIRS could reflect the functional state of the sensory-motor nerve circuit ( Chen Y. F. et al, 2023 ). It should be noted that the team conducted a randomized controlled study.…”
Section: Resultsmentioning
confidence: 99%